You are an Artist (Journal of Parents and Teachers, 2021)
You will not find anything that you do not know in this article, perhaps you have already thought about it, but I did not want to stay without telling you that if you are a teacher, a teacher, or a parent, you have a duty to stop and think about what you are going to teach. "The how" is well studied and changes fast. In fact, "the how" entertains us from our real purpose. Teaching is also an art and you are the artist. The more delicate the work, the more proud you will be of the result.
Keywords: entertainment; learning; boredom; games; new technologies